Studi Karakteristik Tegangan Tembus DC Polaritas Positif Pada Gas Nitrogen (N2) - Pardede, Tumpal; Murdiya, Fri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Insulation of Sulfur hexafluoride (SF6) gas, nitrogen (N2) gas and Carbon Dioxide (CO2) gas usually used in circuit breaker. Sulfur hexafluoride (SF6) gas is widely used in high-voltage system. Sulfur hexafluoride (SF6) gas has a higher dielectric strength than the dielectric strength of air. However, Sulfur hexafluoride (SF6) gas is not environmentally friendly and very impact on global warming.The purpose of this study was to test the breakdown voltage of nitrogen (N2) gas is more environmentally friendly as an alternative to insulation of sulfur hexafluoride (SF6) gas. This study use electrodes balls and needles with a distance of 0.5-2 cm and use pressure of 1-4 bar being tested as much as 20 times the experiment. From the test results obtained that the breakdown voltage electrode bigger balls than the electrode needles. Electrode balls with a distance of 2 cm and a pressure of 4 bar has a value of breakdown voltage greater than 140 kV, while the electrode needles with a distance of 2 cm and a pressure of 4 bar has a breakdown voltage of 79 kV.Keywords : Electrodes, Nitrogen (N2) Gas, Insulation of Gas, Dielectric Strength, Breakdown